Biology and Management of Amaranthus stem borer (Hypolixus truncatulus) (COLEOPTERA: CURCULIONIDAE) - Rajeshkanna, S.; Mikunthan, G. (Annals of Sri Lanka Department of Agriculture., 2017)
Amaranthus stem borer, Hypolixus truncatulus(F.) (Coleoptera: Curculionidae) has become a major problem in Amaranthus cultivations in Mannar and Kilinochchi districts compelling farmers to abandon cultivations. This study was carried out to record its damage symptoms on Amaranthus and economical and safer methods for its management. The important damage was holes on the stems and fecal materials and different larval stages along the stem. Its biology was studied in insect-proof caged plants and plastic containers. Field experiments were conducted in Mannar to determine an efficient method to manage H. truncatulus. Total life cycle of this pest completed in 42.3 ±0.7 days with five larval instars. Egg period, larval period, and pupa period was determined as 3-5 days, 29-32 days, 9-10 days, respectively. Experiment plots treated with boiled Neem seed extract (5% w/v) and Coleus aromaticous leaf extract (20% w/v) recorded significantly lower stem borer populations (0.5 - 0.4 stem borers/ m2) as compared to the untreated control (9.06 stem borers/ m2 ).
Keywords: Amaranthus; Coleus aromaticous; Stem Borer; Hypolixu struncatulus; Neem